497 Targeting Improvements in The Elective Aneurysm Pathway in The Dorset and Wiltshire Vascular Network (DWVN). (4th May 2021) - Cruikshank, N; Harris, L; Richards, S; Metcalfe, J; Page, B; Watson, A; Wijesinghe, L
Abstract: Introduction: Two consecutive NVR reports identified the DWVN as the 7 th slowest network to treat patients with AAAs. We aimed to detect if there were any significant delays in our pathway. Method: We performed a retrospective audit of patients having elective open and endovascular repair. 144 patients who had AAA repair between 30/06/2016-01/08/2018 were included. Data were collected on the following stages: the date the AAA reached ≥55mm, referral date, date clinician reviewed, CT scan date, CPET testing date, MDT date and operation date. The time in days between each stage was recorded and any delays documented. Results: At RBH the longest delay was between MDT and surgery (median 73 days, IQR 32 days-130 days). At DCH the major delay was between CPET and MDT (median 28.5 days, IQR 10 days-31 days). At SDH the longest stage was between MDT and operation (median of 88 days, IQR 37 days-154 days). Examples of reasons for delays across the three hospitals included awaiting specialist opinions, patient being unwell and no ITU beds available. Conclusions: The pathway for elective AAA treatment in the DWVN is slow across all three hospitals. The greatest delay is often between MDT and surgery. Targeting this stage could significantly shorten the pathway.